Ethnomathematical paths to Financial Educacion : analysing cultural traits of Deaf students. - Pinheiro, Rodrigo Carlos (2020)
The results obtained from research look at the cultural traits produced by Deaf students concerning the development of their financial education are in accordance to the perspective of the Ethnomathematics Program. In this article, the authors outline the participants’ profile; and provide a brief description of grounded theory that forms the methodological design used to conduct this study by using specific coding procedures. The authors also emphasize the relation between ethnomathematics and deaf culture through the use of jargon and procedures used by Deaf students in the study of mathematical content related to Financial Education. We also present a diversity of ways of signing the same mathematical content in Brazilian Sign Language (Libras), as well the communicative differences that arise due to the use of these sign variations. The results obtained in this study show that ethnomathematics contributed to the understanding and awareness of the characteristics of Deaf Culture and its relations to school mathematics. Another contribution is that ethnomathematics and its pedagogical action acquired a relevant status in the elaboration of a mathematical curriculum and in the development of financial education for Deaf students.